Professional and personal strategies of documentary filmmakers in Brazil: the case of the State of Rio de Janeiro and Minas Gerais - Autissier, Anne-Marie (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2020)
Between 2012 and 2019, this qualitative sociological research was part of a documentary "boom" moment in Brazil, in terms of production and international recognition. Faced with a bottleneck in terms of their distribution, a growing number of festivals have opened up for documentaries, not counting the historical festival "É tudo Verdade" (São Paulo). This period also corresponds to a time when attempts at policies in favor of documentary films were made by the Federation and the Ministry of Culture (MinC) – public channel TV Brasil, TV Cultura, Doc.TV... These various advances have allowed the expression of a "black" cinema (Joel Zito Araujo), LGBT concerns (Karla Holanda), women’s rights (Helena Solberg and Susanna Lira) and the possibility for indigenous people to seize digital tools to reflect their own realities (Vincent Carelli, Video nas aldeias). Thus, while the Brazilian authorities were carrying out unfinished policies facing the weight of the private oligopolistic sector, it was interesting to analyze how documentary filmmakers developed their professional strategies. From this perspective, fourteen directors were the subject of semi-structured interviews in the state of Rio de Janeiro and three in Minas Gerais. In addition, producers and festival managers were also contacted. But the arrival of the Bolsonaro government caused a real rift. Against a backdrop of cultural war, fake news aimed at discrediting artistic circles, the takeover of the National Cinema Agency (ANCINE) and the abandonment of the São Paulo film library, cuts from major corporate sponsors, and beyond, Brazilian documentary filmmakers have found themselves strangers in their own country.